PENGARUH EXECUTIVE INCENTIVE, FIRM SIZE, DAN LEVERAGE TERHADAP EARNINGS MANAGEMENT PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DALAM BURSA EFEK INDONESIA PERIODE 2015-2018 - Nadhila Ellyane Ardaputri; Dikdik Saleh Sadikin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2021)
This study aims to determine the effect of Executive Incentive, Firm Size, and Leverage on Earnings Management. The object of research in this study is the LQ-45 company listed on the Indonesia Stock Exchange (BEI) in the 2015-2018 period. This research uses purposive sampling method so that 27 companies are obtained with a total of 97 observations after outliers. This study uses a random effect model and multiple regression analysis used in hypothesis testing. This study provides results that the executive incentive LQ-45 company does not affect earnings management; firm size has a positive effect on earnings management; and leverage has no effect on earnings management.